METHODS OF INNOVATIVE DEVELOPMENT OF REGIONAL INDUSTRY (Marketing Journal, 2025)
This article will analyze modern methods of innovative development of the region's industries, their economic efficiency, as well as practical mechanisms. The study analyzes the possibilities of stimulating innovation in 1industrial enterprises, introducing digital technologies and building research potential to optimize econometric and management processes and increase efficiency.
Keywords: Innovation; industrial production; digital economy; innovative infrastructure; technological modernization; econometric model